Bidirectional Control of Behavioral Flexibility by Cholinergic Neurons - Okada, Kana (Brain and nerve = Shinkei kenkyū no shinpo, 2025)
Flexibility enables behaviors and thoughts to adapt to changing environments. The basal ganglia may play a critical role in the suppression and enhancement of flexibility by engaging in parallel and serial processing of several aspects of behavioral flexibility via afferent projections from related brain regions, such as the orbitofrontal cortex and intralaminar nucleus. Previous studies have suggested that the interactions between striatal cholinergic interneurons and these brain regions belong to a neuronal system that provides behavioral flexibility without interfering with existing learning and a new one regarding contingency, probably depending on glutaminergic and dopaminergic cholinergic inputs from the cerebral cortex, intralaminar nucleus, midbrain, and pedunculopontine nucleus. In particular, dorsomedial striatum cholinergic interneurons may exert bidirectional control of behavioral flexibility through neuronal dynamics among related brain areas that contribute to the cognitive subprocesses of flexibility.